PENGARUH KONSENTRASI BOSWELLIC ACID TERHADAP MUTU FISIK SEDIAAN NANO GEL BERBASIS KARBOPOL 940 - Dedi Damhuri; Sri Novianti; Fatati; Jul Andayani (JURNAL BIOSENSE, 2026)
Nanotechnology represents an innovative strategy to enhance the penetration and efficacy of active compounds in topical formulations. This study aimed to formulate and evaluate the physicochemical properties of Boswellic Acid (BA) nano-gel with varying concentrations of the active ingredient using a Carbopol 940-based matrix. The research methodology commenced with particle size reduction of BA through an ultrasonication technique for 150 minutes, followed by its integration into a gel matrix containing propylene glycol and glycerin as humectants. The pharmaceutical quality evaluation included organoleptic, homogeneity, pH, viscosity, spreadability, and drying time tests. The results demonstrated that all formulations (NgBA-F1, NgBA-F2, and NgBA-F3) exhibited excellent homogeneity with a constant pH value of 5, ensuring compatibility with skin physiology. The viscosity of all formulas reached 3000 cPa, meeting the ideal standards, although the concentration of the active ingredient significantly influenced the color intensity of the preparation. However, mechanical testing revealed a spreadability of 3 cm, which did not meet the ideal criteria of 5–7 cm due to high viscosity. Furthermore, the addition of BA extended the drying time to a range of 26.27–28.17 seconds compared to the gel base (15.65 seconds). This study concludes that the Boswellic Acid nano-gel formulation met the physical quality standards for pH, viscosity, and homogeneity, but requires further optimization of the base components to improve spreadability characteristics and drying time kinetics.